SELF AND OTHERS STIGMA, FACE-TO-FACE AND ONLINE ATTITUDE, AND INTENTIONS TO SEEK COUNSELING: A STRUCTURAL EQUATION MODEL - Lorrence Prim; Kurt Willie Janaban; Teresita Rungduin; Darwin Rungduin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The effect of personal and perceived stigmatization on attitudes towards counseling in face-to-face and online modalities, as well as the intent to seek school counseling, was investigated in this study. The researchers used a descriptive correlational and quasi-experimental research design to come up with a structural equation model. 439 participants completed the survey measuring self-stigma, perceived stigma, attitudes in face-to-face and online counseling, and counseling-seeking intentions. Results indicated that self-stigma and perceived stigma were negatively associated with attitudes toward face-to-face and online counseling, as well as intentions to seek counseling. Attitudes toward counseling in face-to-face modality were positively related to intentions to seek counseling, while attitudes toward online counseling did not significantly affect intentions. From this, a structural equation model was generated. It indicates that stigmatization by others predicts the stigmatization by self and influences how comfortable adolescents are with counseling in both online and face-to-face modalities. This stigmatization by self and discomfort then predicts the way adolescents place importance on the two counseling modalities which in turn predicts the level of school counseling-seeking intention they have for various concerns. These findings highlight the importance of addressing stigma to promote positive attitudes toward counseling and increase help-seeking intentions.